The EXCITE Trial: Reacquiring Upper-Extremity Task Performance With Early Versus Late Delivery of Constraint Therapy. (September 2013) - Lang, Kimberly C.; Thompson, Paul A.; Wolf, Steven L.
Objective. This study examines performance of Wolf Motor Function Test (WMFT) tasks in terms of the ability of EXCITE trial participants (who had suffered a stroke 3-9 months before recruitment) to complete the task within the timed interval. Methods. Data were collected from participants who received constraint-induced movement therapy (CIMT) 3 to 9 months poststroke (CIMT-I, n = 106) or 15 to 21 months poststroke (CIMT-D, n = 116). Performance on the 15 timed WMFT tasks was converted into binary values, and changes in completion of the tasks were analyzed with generalized estimating equation methods, under the assumption of a binomial or Poisson process for completion. Results. During CIMT, the CIMT-I group showed significant within-group improvements in 3 fine-movement tasks and in total noncompleted tasks ( noncompletes ), whereas the CIMT-D group did not ( P ≤ .0036). CIMT-I improvement was significantly greater than CIMT-D improvement for the lifting pencil task and total noncompletes. During the year following CIMT, neither group showed significant changes in completion of WMFT tasks. Over all time intervals, only the CIMT-I group displayed significant improvement in several tasks and total noncompletes. Between groups, there were significant and almost-significant differences between the improvements of the 2 groups in 3 tasks requiring fine distal movement. Conclusion. Receiving CIMT earlier appears to improve reacquisition and retention of WMFT tasks, especially those requiring fine motor skills. Combined with earlier findings, these results indicate that improvements in existing motor abilities are possible with both immediate and delayed CIMT, but early CIMT is necessary for significant reacquisition of tasks.